Heterojunction nano composite material as well as preparation method and application thereof

By using C3N4/MoS2/titanium dioxide nanotube heterojunction nanocomposites, the existing photocatalytic composite materials are solved, and the existing photocatalytic composite materials are low efficiency and difficult to synthesize when dealing with organic pollutants, and efficient photocatalytic and organic pollutant removal are achieved. .

CN119406439AActive Publication Date: 2025-02-11CHANGSHA ENVIRONMENTAL PROTECTION COLLEGE
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411537551.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-11
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

Existing photocatalytic composite materials are less efficient when dealing with organic pollutants and are more difficult to synthesis.

Method used

Using C3N4/MoS2/titanium dioxide nanotube heterojunction nanocomposite, a heterojunction nanocomposite with petal sheet-shaped MoS2 nanosheets and highly directionally grown titanium dioxide nanotubes were prepared by hydrothermal reaction and high-temperature treatment.

Benefits of technology

It improves photocatalytic efficiency, enhances carrier transmission, reduces the recombination of electron-hole pairs, solves the problem of carrier transport restrictions, and achieves the effect of efficiently removing organic pollutants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119406439A_ABST
    Figure CN119406439A_ABST
Patent Text Reader

Abstract

The invention provides a heterojunction nano composite material and a preparation method and application thereof, the heterojunction nano composite material comprises C3N4 / MoS2 / titanium dioxide nanotube heterojunction nano particles, and the C3N4 / MoS2 / titanium dioxide nanotube heterojunction nano particles are MoS2 / titanium dioxide mixed bodies of which the surface layers are coated with layered C3N4; wherein in the MoS2 / titanium dioxide mixed body, the titanium dioxide nanotubes grow in a highly oriented manner; the MoS2 nanosheets are in a petal sheet shape and are uniformly distributed on the surfaces of the titanium dioxide nanotubes. The material is stable in structure and high in organic pollutant removal efficiency; the preparation method is safe and simple, mild in reaction and low in toxicity, has the advantages of environmental friendliness, safety and controllability, is easy for large-scale production, and brings great innovation to future new energy development and environmental governance; the method is suitable for large-area popularization and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of environmental governance and restoration materials, and in particular to a heterojunction nanocomposite material and a preparation method and application thereof. Background Art

[0002] With the rapid development of industrialization, various persistent organic pollutants, such as p-nitrophenol, methyl orange, methylene blue, phenol, rhodamine, fluorescent yellow, 2,4-dichlorophenoxyacetic acid, etc., are excessively discharged into the environment. According to a large number of studies, these chemicals are persistent, have the ability to migrate over long distances and bioaccumulate, and therefore may pose potential hazards to ecosystems and human health.

[0003] TiO2 is a direct wide bandgap semiconductor material (3.2eV). In order to promote the research of TiO2 materials in the field of light energy conversion, it is necessary to perform multiple sensitizations on it to expand the light response range of the material and ultimately improve the light conversion efficiency. The commonly used photosensitizers in the prior art are narrow-band semiconductor materials, such as CdS, CdSe, Fe2O3 and CdTe; precious metal semiconductors, such as Bi2MoO6, BiOBr, Ag3PO4, etc. However, they all have problems such as poor stability and high production costs due to the presence of precious metal elements.

[0004] Research has confirmed that the use of different sensitizers to modify the material can not only expand the light response range of the material to the visible and near-infrared regions, but also provide a patchwork band gap structure to promote carrier transmission and be used to remove organic pollutants. However, the existing modified materials have low light utilization, poor organic pollutant removal efficiency, and are difficult to synthesize. Summary of the invention

[0005] The main purpose of the present invention is to provide a heterojunction nanocomposite material and a preparation method and application thereof, aiming to solve the problems of low efficiency in treating organic pollutants and high difficulty in material synthesis in the prior art using photocatalytic composite materials.

[0006] To achieve the above-mentioned purpose, the present invention provides a heterojunction nanocomposite material, which includes C3N4 / MoS2 / titanium dioxide nanotube heterojunction nanoparticles, and the C3N4 / MoS2 / titanium dioxide nanotube heterojunction nanoparticles are MoS2 / titanium dioxide hybrids with layered C3N4 coated on the surface; wherein, in the MoS2 / titanium dioxide hybrid, the titanium dioxide nanotubes are highly directionally grown; and the MoS2 nanosheets are in the shape of petals and are uniformly distributed on the surface of the titanium dioxide nanotubes.

[0007] The present invention also provides a method for preparing the heterojunction nanocomposite material as described above, comprising the steps of: providing a molybdenum-sulfur solution; the molybdenum-sulfur solution is an aqueous solution containing a molybdenum source substance and a sulfur source substance; wherein the molar ratio of the molybdenum element to the sulfur element in the molybdenum-sulfur solution is 1-3:15-20.

[0008] Titanium dioxide nanotubes are added to the molybdenum-sulfur solution for hydrothermal reaction to obtain a MoS2 / titanium dioxide hybrid; wherein, in the MoS2 / titanium dioxide hybrid, the titanium dioxide nanotubes are highly directionally grown; and the MoS2 nanosheets are in a petal-like morphology and are evenly distributed on the surface of the titanium dioxide nanotubes.

[0009] Provide a C3N4 dispersion; immerse the MoS2 / titanium dioxide hybrid in the C3N4 dispersion for high-temperature treatment to obtain a heterojunction nanocomposite material; wherein the temperature of the high-temperature treatment is 150 to 200°C; and the duration of the high-temperature treatment is 4 to 6 hours.

[0010] Furthermore, the molybdenum source material includes one or more of molybdenum trioxide, ammonium molybdate and sodium molybdate.

[0011] Furthermore, the sulfur source material is C2H5NS.

[0012] Furthermore, the temperature of the hydrothermal reaction is 180-220° C.; the duration of the hydrothermal reaction is 6-24 hours.

[0013] Furthermore, the C3N4 dispersion is obtained by sequentially subjecting the nitrogen-containing organic matter to high-temperature calcination, grinding, protonation and ultrasonic dispersion treatment to obtain the C3N4 dispersion; wherein the nitrogen-containing organic matter includes one or more of melamine, cyanuric acid, melamine resin and urea.

[0014] Furthermore, the temperature of the high temperature calcination treatment is 450-550° C.; and the duration of the high temperature calcination treatment is 12-24 hours.

[0015] Furthermore, after the high temperature treatment step, the product after the high temperature treatment is further subjected to washing and vacuum drying to obtain the heterojunction nanocomposite material.

[0016] The present invention also provides an application of the heterojunction nanocomposite material as described above or a heterojunction nanocomposite material prepared by any one of the preparation methods described above, wherein the heterojunction nanocomposite material is inserted into an organic pollutant solution as a working electrode, and subjected to visible light irradiation treatment to obtain a pollutant decomposed liquid; wherein the visible light has a wavelength of 400 to 800 nm, and the duration of the visible light irradiation treatment is 30 to 80 min.

[0017] Furthermore, the concentration of the organic pollutant solution is 10-50 mg / L; the organic pollutant solution includes one or more of p-nitrophenol, methyl orange, methylene blue, phenol, rhodamine, fluorescent yellow, and 2,4-dichlorophenoxyacetic acid.

[0018] The beneficial effects achieved by the present invention are:

[0019] The heterojunction nanocomposite provided by the present invention can realize the transfer of charge and energy of the heterojunction nanocomposite by using a light source in the visible light band. The MoS2 in the heterojunction nanocomposite has a strong adsorption capacity, and the heterostructure of the heterojunction nanocomposite formed has a step-by-step energy level structure that matches the energy thereof. The formation of the energy band between the MoS2 nanosheet, C3N4 and the titanium dioxide nanotube is more conducive to the transmission of charge carriers, reduces the recombination of electron-hole pairs, and solves the problem of carrier transport limitation. Moreover, the structure of the heterojunction nanocomposite is stable, which is beneficial to the efficient removal of organic pollutants.

[0020] The preparation method of the heterojunction nanocomposite provided by the present invention is simple and efficient to prepare a high-performance multi-element energy band optimally matched optoelectronic material (heterojunction nanocomposite) under the premise of low production cost. The preparation method has a high preparation yield, uniform product morphology, high stability, and solves the problems of complex nano-process, easy product agglomeration, large particle size, etc., and the equipment used in the preparation process is low in price, the operation steps are safe and simple, the reaction is mild, and the toxicity is low. It has the advantages of being environmentally friendly, safe and controllable, and is easy to mass produce, bringing major innovations to future new energy development and environmental governance.

[0021] The heterojunction nanocomposite material provided by the present invention is applied to the treatment of organic pollutant solution, and the material is directly inserted into the organic pollutant solution as a working electrode, and irradiated with visible light (with a wavelength of 400 to 800 nm) for 30 to 80 minutes. The treatment process is simple, the reaction time is short, the energy consumption is low, the removal efficiency of organic pollutants is high, and it is suitable for large-scale promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0023] Figure 1 This is a characterization analysis diagram of the heterojunction nanocomposite material prepared in Example 1 of the present invention; wherein, Figure 1(a) is a transmission electron microscope (TEM) image of the material at a scale of 100 nm; Figure 1 (b) Figure 1 (a) is a 2x magnified image; Figure 1 (c) is a scanning electron microscope (SEM) image of the material at a scale of 500 nm; Figure 1 (d) Figure 1 (c) 2.5 times magnification; Figure 1 (e) is a high-resolution transmission electron microscopy (HRTEM) image of the material;

[0024] FIG2 is an X-ray photoelectron spectrum (XPS) diagram of the heterojunction nanocomposite material prepared in Example 2 of the present invention; wherein FIG2(a) is a full spectrum diagram of the X-ray photoelectron spectrum (XPS) of the material; FIG2(b) is a high-resolution X-ray photoelectron spectrum (XPS) diagram of C1s, O 1s, Ti 2p, N 1s, Mo 3d and S 2p of the material;

[0025] Figure 3 This is an energy dispersive X-ray (EDX) spectrum analysis diagram of the heterojunction nanocomposite material prepared in Example 1 of the present invention;

[0026] Figure 4 This is a diagram showing the catalytic degradation effect of the heterojunction nanocomposite material on Rh B in Example 3 of the present invention;

[0027] Figure 5 This is a comparison chart of the catalytic degradation effects of different materials on Rh B in Example 3 of the present invention; wherein, Figure 5 (a) is a comparison chart of the catalytic degradation effect of each material on Rh B at different times; Figure 5 (b) is a comparison chart of the degradation kinetic rates of each material to Rh B;

[0028] Figure 6 This is a comparison diagram of four cycles of catalytic degradation of Rh B by the heterojunction nanocomposite material in Example 3 of the present invention;

[0029] Figure 7 This is a diagram showing the catalytic degradation effect of the heterojunction nanocomposite material on PNP in Example 4 of the present invention;

[0030] Figure 8 This is a comparison chart of the catalytic degradation effects of different materials on PNP in Example 4 of the present invention; wherein, Figure 8 (a) is a comparison chart of the catalytic degradation effect of each material on PNP at different time periods; Figure 8 (b) is a comparison diagram of the degradation kinetic rates of PNP by various materials;

[0031] Fig. 9This is a comparison diagram of four cycles of catalytic degradation of PNP by the heterojunction nanocomposite material in Example 4 of the present invention;

[0032] Fig.10 The UV-visible absorption spectrum analysis comparison diagram of the heterojunction nanocomposite material, TiO2, TiO2 / MOS2, and TiO2 / C3N4 in the analysis example 4 of the present invention is shown; wherein, Fig.10 (a) is a comparison of the ultraviolet-visible (UV-vis) absorption spectra of various materials; Fig.10 (b) is a comparison chart of the corresponding Kubelka-Munk transformed reflectance spectra.

[0033] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with the implementation methods and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] It should be noted that, in the absence of conflict, the following embodiments and features in the embodiments can be combined with each other. It should also be understood that the terms used in the embodiments of the present invention are intended to describe specific embodiments rather than to limit the scope of protection of the present invention.

[0036] Unless otherwise defined, all technical and scientific terms used in the present invention are consistent with the prior art mastery of the technicians in this field and the records of the present invention. Any methods, equipment and materials of the prior art similar to or equivalent to the methods, equipment and materials described in the embodiments of the present invention can also be used to implement the present invention. It should be known to those skilled in the art that, as an explanation of the present application document, without affecting the actual understanding of the technical solution of the present application, "Binding Energy" can be expressed as binding energy, "Intensity" can be expressed as intensity, "Wavelength" can be expressed as wavelength, "Absorbance" can be expressed as absorbance, "Removal efficiency of Rh B" can be expressed as the catalytic degradation efficiency of Rh B, and "In(C0 / C t )” can be expressed as the relationship between the concentration of the reactant and time (especially in the first-order kinetic process, the concentration of the reactant decays exponentially with time, at this time In(C0 / C t ) is proportional to the reaction time t), "C t“ / C0” can be expressed as instantaneous concentration / original concentration, and “Removal efficiency of PNP” can be expressed as the removal efficiency of PNP.

[0037] When the embodiments give numerical ranges, it should be understood that unless otherwise specified in the present invention, both endpoints of each numerical range and any value between the two endpoints can be selected. The test methods in the following embodiments without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturers. The materials or reagents required in the following embodiments are commercially available unless otherwise specified.

[0038] In order to solve the problems of low efficiency in treating organic pollutants and high difficulty in material synthesis in the prior art using photocatalytic composite materials, the present invention provides a heterojunction nanocomposite material, which includes C3N4 / MoS2 / titanium dioxide nanotube heterojunction nanoparticles. The C3N4 / MoS2 / titanium dioxide nanotube heterojunction nanoparticles are MoS2 / titanium dioxide hybrids with layered C3N4 coated on the surface; wherein, in the MoS2 / titanium dioxide hybrid, the titanium dioxide nanotubes are highly directionally grown; and the MoS2 nanosheets are petal-like morphology and are evenly distributed on the surface of the titanium dioxide nanotubes.

[0039] Specifically, the titanium dioxide nanotubes are highly directional, with a tube diameter of about 80nm and a tube wall thickness of about 10nm. MoS2 nanosheets with petal-like morphology are thinly and evenly distributed on the surface of the titanium dioxide nanotubes. MoS2 nanosheets are mainly attached to the junction between the titanium dioxide nanotubes. Although the loading amount is large, the titanium dioxide nanotube array maintains the characteristic of opening at the top. This structure is conducive to the transmission of photogenerated electrons and the adsorption of degraded substances.

[0040] It should be noted that the heterojunction nanocomposite material is MoS2 with petal-like morphology and layered C3N4, and two semiconductor material films with different electronic band structures are sequentially deposited on titanium dioxide nanotubes to form a heterojunction nanocomposite material.

[0041] Studies have found that the electron mobility of MoS2 is higher than that of titanium dioxide. A variety of MoS2 nanostructures can be grown directly on TiO2 substrates through simple and low-cost chemical routes, such as zero-dimensional nanospheres, one-dimensional nanowires, two-dimensional nanoplates and three-dimensional porous multilayer nanoplates. However, zero-dimensional nanospheres: The preparation process is complicated and it is difficult to control the particle size and morphology. One-dimensional nanowires: They are easy to agglomerate during the preparation process, resulting in performance degradation. Two-dimensional nanoplates: High temperature and high pressure are required during the preparation process, which is costly. Three-dimensional porous multilayer nanoplates: The preparation process is complicated and requires special equipment and technology. "In the MoS2 / titanium dioxide hybrid, titanium dioxide nanotubes are highly oriented; MoS2 nanosheets have a petal-like morphology and are evenly distributed on the surface of titanium dioxide nanotubes." The titanium dioxide nanotube array maintains the characteristic of opening at the top, which is conducive to the transmission of photogenerated electrons and the adsorption of degraded substances. The composite efficiency of MoS2 and titanium dioxide is effectively improved, and the interaction between the two is enhanced; the petal-shaped MoS2 nanosheets and the embedded titanium dioxide nanotubes form a unique structure, which is conducive to improving the photocatalytic performance; the MoS2 / titanium dioxide hybrid can effectively separate and transfer electron-hole pairs, reduce the probability of recombination, and improve the quantum efficiency; the MoS2 and titanium dioxide in the hybrid can work synergistically to improve the selectivity and activity of the photocatalytic reaction. C3N4 (graphite phase carbon nitride) is a non-metallic semiconductor material. It is an organic polymer with a unique two-dimensional layered structure, which is composed of carbon and nitrogen atoms connected by covalent bonds. It can produce electron-hole pairs under visible light irradiation, which is used to catalyze reactions such as water decomposition to produce hydrogen and degradation of organic pollutants. C3N4 is also a direct bandgap semiconductor with a bandgap width of about 2.9eV, which means that it can only absorb photons with energy higher than its bandgap. In the visible light range, the energy of most photons is lower than the bandgap energy of C3N4, so the efficiency of C3N4 in photocatalytic reactions under visible light is low.

[0042] However, the heterojunction nanocomposite material (C3N4 / MoS2 / titanium dioxide nanotube heterojunction nanoparticles) obtained by the present invention can significantly improve the photocatalytic efficiency; the reasons are analyzed as follows:

[0043] (1) Synergistic effect of band structure: The band structure of MoS2 and titanium dioxide works synergistically with the band structure of C3N4, allowing the composite material to absorb light in a wider wavelength range. The band gap width of MoS2 is about 1.9eV, while the band gap width of titanium dioxide is about 3.2eV. By compounding C3N4 with MoS2 and titanium dioxide, MoS2 can be used to absorb visible light, while C3N4 and titanium dioxide can only absorb near-ultraviolet light, thereby red-shifting the light absorption range and expanding it to the visible light absorption range. Visible light accounts for about 50% of the total energy of solar radiation, while ultraviolet light accounts for about 7% of the total energy of solar radiation. The composite material improves the utilization rate of solar energy.

[0044] (2) Separation of electron-hole pairs: The composite between C3N4, MoS2 and titanium dioxide can improve the separation efficiency of electron-hole pairs. In the photocatalytic process, the separation of electron-hole pairs is the key to improving the catalytic efficiency. The composite of C3N4, MoS2 and titanium dioxide (heterojunction nanocomposite) can provide an effective electron-hole pair separation mechanism, reduce the charge recombination inside the composite, and thus improve the catalytic activity.

[0045] (3) Enhanced light absorption and light scattering: Different materials in the composite material can interact with each other to enhance light absorption and scattering. This helps to improve light utilization and further enhance photocatalytic efficiency.

[0046] (4) Synergistic catalysis: The synergistic effect between C3N4, MoS2 and titanium dioxide can promote specific catalytic reactions. For example, MoS2 can act as an electron donor to help C3N4 and titanium dioxide accelerate specific redox reactions, thereby improving catalytic performance.

[0047] By compounding C3N4 with MoS2 and titanium dioxide, the advantages of each can be utilized to overcome the limitations of a single material, thereby achieving more efficient and comprehensive photocatalytic performance.

[0048] The heterojunction nanocomposite provided by the present invention can realize the transfer of charge and energy of the heterojunction nanocomposite by using a light source in the visible light band. The MoS2 in the heterojunction nanocomposite has a strong adsorption capacity, and the heterostructure of the heterojunction nanocomposite formed has a step-by-step energy level structure that matches the energy thereof. The formation of the energy band between the MoS2 nanosheet, C3N4 and the titanium dioxide nanotube is more conducive to the transmission of charge carriers, reduces the recombination of electron-hole pairs, and solves the problem of carrier transport limitation. Moreover, the structure of the heterojunction nanocomposite is stable, which is beneficial to the efficient removal of organic pollutants.

[0049] The present invention also provides a method for preparing the heterojunction nanocomposite material as above, comprising the steps of: providing a molybdenum-sulfur solution; the molybdenum-sulfur solution is an aqueous solution containing a molybdenum source substance and a sulfur source substance; wherein the molar ratio of the molybdenum element to the sulfur element in the molybdenum-sulfur solution is 1-3:15-20. Specifically, the source substance in the molybdenum-sulfur solution and the sulfur source substance undergo a chemical reaction: Mo 4+ +2S 2- →MoS2. When the molar ratio of molybdenum to sulfur in the molybdenum-sulfur solution is 1-3:15-20, the reactants can be ensured to react fully, avoiding excessive or insufficient sulfur, which affects the formation and purity of molybdenum disulfide. If the molar ratio of molybdenum to sulfur is too high, excessive sulfur may cause the sulfur content in the generated molybdenum disulfide to be too high, affecting its performance; if the molar ratio is too low, excessive molybdenum may cause the molybdenum content in the generated molybdenum disulfide to be too high, also affecting its performance.

[0050] Titanium dioxide nanotubes are added to a molybdenum-sulfur solution for a hydrothermal reaction to obtain a MoS2 / titanium dioxide hybrid; wherein, in the MoS2 / titanium dioxide hybrid, the titanium dioxide nanotubes grow in a highly directional manner; the MoS2 nanosheets have a petal-like morphology and are evenly distributed on the surface of the titanium dioxide nanotubes.

[0051] Specifically, the petal-shaped MoS2 nanosheets have good visible light absorption, while the titanium dioxide nanotubes have a good response in the ultraviolet region. The energy band structure of MoS2 matches that of titanium dioxide nanotubes, allowing photogenerated electrons and holes to be effectively transferred and separated; the combination of the two can broaden the light absorption range and improve the photocatalytic efficiency.

[0052] Moreover, a heterojunction is formed between MoS2 nanosheets and titanium dioxide nanotubes, generating a built-in electric field and promoting charge separation. Among them, the interface contact between MoS2 nanosheets and titanium dioxide nanotubes is conducive to the rapid separation and transfer of charges, reducing charge recombination, thereby further enhancing the photocatalytic activity and improving charge separation and transfer.

[0053] The petal-shaped morphology of MoS2 nanosheets may introduce certain surface defects, which can serve as active sites to promote the photocatalytic reaction. Therefore, the embedding of MoS2 nanosheets can also enhance the structural stability of the composite material, allowing it to maintain good performance and enhance stability during long-term use. In addition, the petal-shaped MoS2 nanosheets increase the specific surface area of ​​the material, which helps to adsorb pollutants and increase the rate of photocatalytic reaction.

[0054] In addition, it was found during the experiment that if the morphology of MoS2 is not petal-like, it may not be able to form a good embedded structure with titanium dioxide nanotubes, affecting charge transfer and synergy. Under certain extreme conditions, MoS2 and titanium dioxide may react chemically, destroying the structure and properties of the composite material, and there are chemical compatibility issues. Moreover, MoS2 nanosheets with non-petal-like morphology will affect the loading amount. Too high or too low a loading amount of MoS2 nanosheets may affect the performance of the final composite material. Too high a loading amount may lead to agglomeration, reduce the specific surface area and light transmittance; too low a loading amount cannot fully exert the synergistic effect.

[0055] In an optional embodiment, a sheet of titanium metal is etched by wet chemical etching to obtain a vertically grown three-dimensional porous structure of titanium dioxide nanotubes. The three-dimensional porous structure of the titanium dioxide nanotubes gives it a higher specific surface area, which is conducive to enhancing its catalytic, adsorption and sensing properties. Moreover, the porous structure provides more active sites, so that the titanium dioxide nanotubes have excellent catalytic activity and good biocompatibility in catalytic reactions. In addition, this porous structure can change the propagation path of light in the material, enhancing the light absorption and luminescence properties of the composite material.

[0056] In addition, the three-dimensional porous structure of titanium dioxide nanotubes can provide certain mechanical support, making the final composite material more durable during application. The porous structure of titanium dioxide nanotubes also facilitates the introduction of MoS2 nanosheets and C3N4 in the subsequent preparation process steps, thereby realizing the functionalization of the composite material.

[0057] Among them, wet chemical etching is environmentally friendly and does not produce harmful organic solvents and gases. It is also simple to prepare, can be carried out under laboratory conditions, and is easy to scale up for production. Moreover, the use of metallic titanium as a precursor is low in cost, and the wet chemical etching process does not require expensive equipment.

[0058] Provide a C3N4 dispersion; immerse a MoS2 / titanium dioxide hybrid in the C3N4 dispersion for high temperature treatment to obtain a heterojunction nanocomposite material; wherein the temperature of the high temperature treatment is 150 to 200°C; and the duration of the high temperature treatment is 4 to 6 hours. Specifically, in order to obtain a well-dispersed C3N4 dispersion, a concentrated hydrochloric acid solution is used to protonate the C3N4. The protonated C3N4 is beneficial for coating the C3N4 on the surface of the titanium dioxide nanotubes due to stacking breaks and the formation of small C3N4 particles. After loading MoS2 and C3N4 nanoparticles, the structural integrity and morphology of TiO2 NTAs remain unchanged.

[0059] Among them, at 150-200°C, the molecules in the C3N4 dispersion can penetrate into the surface or interior of the MoS2 / titanium dioxide hybrid, forming chemical bonds or physical adsorption, thereby promoting the interaction between the materials. This interfacial effect can enhance the bonding strength of the materials and improve the performance of the composite material.

[0060] The temperature of 150-200℃ helps to eliminate the internal defects of the material, promote the phase change process, and form a more stable crystal structure. For MoS2 and titanium dioxide, this temperature range may help to form a more stable phase and improve the thermal stability of the material. Moreover, since MoS2 and titanium dioxide are both semiconductor materials, the adjustment of their band structure is crucial to the photoelectric properties of the composite material. High temperature treatment may improve the photoelectric conversion efficiency of the composite material by changing the electronic state density on the surface of the material and optimizing the band structure. Ultimately, the defects inside the prepared material are reduced, and the bonding force between the grains is enhanced, thereby improving the mechanical properties of the composite material, such as strength and toughness; the optimized band structure and interface state can significantly improve the photoelectric properties of the composite material, such as light absorption efficiency and photoelectric conversion efficiency; the internal structure of the material is optimized, which improves the thermal stability of the composite material, so that it can still maintain good performance in a high temperature environment.

[0061] If the temperature is too high, it may cause irreversible chemical reactions in the material, such as the decomposition of C3N4 or the oxidation of MoS2, thereby destroying the structure of the final composite material. If the treatment time is too long, the material surface may overheat, causing thermal damage and affecting the performance of the material. The compatibility of the C3N4 dispersion and the MoS2 / titanium dioxide hybrid is also an important factor for the success of this preparation process. Incompatible materials may undergo harmful reactions during high-temperature treatment and destroy the structure of the composite material. In summary, by reasonably selecting the high-temperature treatment temperature (150-200°C) and treatment time (4-6h), heterojunction nanocomposites with enhanced mechanical properties, improved optoelectronic properties and enhanced thermal stability can be effectively prepared.

[0062] The preparation method of the heterojunction nanocomposite provided by the present invention is simple and efficient to prepare a high-performance multi-element energy band optimally matched optoelectronic material (heterojunction nanocomposite) under the premise of low production cost. The preparation method has a high preparation yield, uniform product morphology, high stability, and solves the problems of complex nano-process, easy product agglomeration, large particle size, etc., and the equipment used in the preparation process is low in price, the operation steps are safe and simple, the reaction is mild, and the toxicity is low. It has the advantages of being environmentally friendly, safe and controllable, and is easy to mass produce, bringing major innovations to future new energy development and environmental governance.

[0063] Further, the molybdenum source material includes one or more of molybdenum trioxide, ammonium molybdate and sodium molybdate. Preferably, the molybdenum source material is sodium molybdate (Na2MoO4·2H2O). Sodium molybdate (Na2MoO4·2H2O) is a high-purity molybdenum compound that can provide a high-purity molybdenum source, and the prepared MoS2 has high purity; and under the experimental conditions of the present invention, sodium molybdate is more likely to promote the formation of MoS2 with a petal-like morphology. And sodium molybdate is easy to dissolve in the solution, which is convenient for mixing with other reactants, thereby simplifying the preparation process. Sodium molybdate is usually easy to separate from the solution by simple filtration or centrifugation after the reaction, which is convenient for subsequent washing and drying steps. This easy handling makes sodium molybdate a preferred raw material for synthesizing MoS2. Using sodium molybdate as a molybdenum source can be carried out under relatively mild reaction conditions, such as lower temperature and pressure, which helps to reduce energy consumption and simplify equipment requirements. And sodium molybdate has good solubility in water, which is conducive to the use of an aqueous phase synthesis method, which is generally environmentally friendly and reduces the need for waste generation and treatment. It also has a lower price, and using sodium molybdate as a raw material is more cost-effective.

[0064] Furthermore, the sulfur source is C2H5NS. Specifically, in the process of synthesizing MoS2, the selection and addition amount of the sulfur source have a great influence on the quality of the final product; sodium molybdate can react with C2H5NS to provide a uniform and controllable sulfur source, which helps to accurately control the composition and structure of MoS2.

[0065] Furthermore, the temperature of the hydrothermal reaction is 180-220° C.; the duration of the hydrothermal reaction is 6-24 hours.

[0066] Furthermore, the C3N4 dispersion is obtained by sequentially subjecting the nitrogen-containing organic matter to high-temperature calcination, grinding, protonation and ultrasonic dispersion to obtain a C3N4 dispersion; wherein the nitrogen-containing organic matter includes one or more of melamine, cyanuric acid, melamine resin and urea. Specifically, in an optional embodiment, melamine is calcined at high temperature in a muffle furnace, and the obtained yellow agglomerate is ground into powder. The protonation treatment is carried out by treating with hydrochloric acid at room temperature for 4 to 6 hours. The protonated C3N4 is then washed with deionized water until it is neutral and dried. Deionized water is ultrasonically dispersed for 6 to 8 hours to obtain a uniformly dispersed C3N4 dispersion.

[0067] Furthermore, the temperature of the high temperature calcination treatment is 450-550° C.; and the duration of the high temperature calcination treatment is 12-24 hours.

[0068] Furthermore, after the high temperature treatment step, the high temperature treatment product is further subjected to washing and vacuum drying to obtain the heterojunction nanocomposite material. Specifically, the high temperature treatment product is washed three times with deionized water and vacuum dried to obtain the heterojunction nanocomposite material.

[0069] The present invention also provides an application of the heterojunction nanocomposite material as above or a heterojunction nanocomposite material prepared by any one of the preparation methods as above, wherein the heterojunction nanocomposite material is inserted into an organic pollutant solution as a working electrode, and is subjected to visible light irradiation treatment to obtain a pollutant decomposed liquid; wherein the visible light has a wavelength of 400 to 800 nm, and the visible light irradiation treatment lasts for 30 to 80 minutes.

[0070] Specifically, 50-100 mL of organic pollutant solution can be added to a cubic quartz cup, and the heterojunction nanocomposite material is inserted into the quartz cup as a working electrode, and irradiated with visible light in the wavelength range of 400-800 nm; the solution is stirred at room temperature, the rotor speed is 50-200 rpm, and sampling is performed every 10 minutes, with a sampling volume of 250 μL-350 μL; detection is performed using an ultraviolet spectrophotometer, and an organic pollutant removal curve is drawn based on the results. Specifically, the visible light source: simulated sunlight xenon lamp (500W Xe lamp, Beijing Changtuo) + UV-cut filter, the light band is 400-800 nm. Light intensity: 100 mW / cm 2 , the measuring instrument is NOVA Oriel 70260. The heterojunction nanocomposite material provided by the present invention is applied to the treatment of organic pollutant solution, the material is directly inserted into the organic pollutant solution as a working electrode, and the visible light irradiation treatment is performed for 30 to 80 minutes. The treatment process is simple, the reaction time is short, the energy consumption is low, the removal efficiency of organic pollutants is high, and it is suitable for large-scale promotion and application.

[0071] Furthermore, the concentration of the organic pollutant solution is 10-50 mg / L; the organic pollutant solution includes one or more of p-nitrophenol, methyl orange, methylene blue, phenol, rhodamine, fluorescent yellow, and 2,4-dichlorophenoxyacetic acid.

[0072] For further understanding of the present invention, examples are given below:

[0073] Example 1

[0074] Sodium molybdate and C2H5NS were used to prepare a molybdenum-sulfur solution in a molar ratio of 1:15;

[0075] Add titanium dioxide nanotubes to the molybdenum-sulfur solution for hydrothermal reaction (180°C; 24h) to obtain MoS2 / titanium dioxide hybrid;

[0076] Using melamine, high temperature roasting treatment (450° C.; 24 hours), grinding treatment, protonation treatment and ultrasonic dispersion treatment are sequentially performed to provide a C3N4 dispersion;

[0077] The MoS2 / titanium dioxide hybrid is immersed in the C3N4 dispersion for high temperature treatment (150°C; 6h), and then the product after high temperature treatment is washed and vacuum dried to obtain a heterojunction nanocomposite material.

[0078] Example 2

[0079] Sodium molybdate and C2H5NS were used to prepare a molybdenum-sulfur solution in a molar ratio of 3:20;

[0080] Adding titanium dioxide nanotubes to the molybdenum-sulfur solution for hydrothermal reaction (220°C; 6h) to obtain MoS2 / titanium dioxide hybrid;

[0081] Using melamine, high temperature roasting treatment (550°C; 12h), grinding treatment, protonation treatment and ultrasonic dispersion treatment are carried out in sequence to provide a C3N4 dispersion;

[0082] The MoS2 / titanium dioxide hybrid is immersed in the C3N4 dispersion for high temperature treatment (200°C; 4h), and then the product after high temperature treatment is washed and vacuum dried to obtain a heterojunction nanocomposite material.

[0083] Analysis example 1

[0084] The heterojunction nanocomposite material prepared in Example 1 was characterized and analyzed, and a transmission electron microscope (TEM) image at a scale of 100 nm was obtained. Figure 1 (a) Figure 1 (b) Yes Figure 1 (a) is a 2x magnified image; Figure 1 (c) is a scanning electron microscope (SEM) image of the heterojunction nanocomposite material at a scale of 500 nm; Figure 1 (d) Yes Figure 1 (c) 2.5 times magnification; Figure 1 (e) is a high-resolution transmission electron microscopy (HRTEM) image of the heterojunction nanocomposite.

[0085] from Figure 1 (a) It can be seen that the petals are MoS2, and the black layer in the middle is C3N4. Figure 1 (b) shows that MoS2 nanosheets are thinly and evenly distributed on the surface of TiO2 nanotubes. MoS2 nanosheets are mainly attached to the junction area between nanotubes, maintaining the open top feature of the TiO2 nanotube array, which is conducive to the transmission of photogenerated electrons and the adsorption of degraded products. Protonated C3N4 is coated on the surface of TiO2 nanotubes. After loading MoS2 and C3N4 nanoparticles, the structural integrity and morphology of TiO2NTAs remain unchanged.

[0086] Figure 1 (c) depicts a scanning electron microscope (SEM) image of the heterojunction nanocomposite, showing that MoS2 nanosheets are thinly and evenly distributed on the surface of TiO2 nanotubes. MoS2 nanosheets are mainly attached to the junction area between nanotubes, maintaining the open top feature of the TiO2 nanotube array, which is conducive to the transmission of photogenerated electrons and the adsorption of degraded products. Protonated C3N4 is coated on the surface of TiO2 nanotubes. After loading MoS2 and C3N4 nanoparticles, the structural integrity and morphology of TiO2 NTAs remain unchanged. Figure 1 (d) shows the magnified TiO2 nanotubes. The obtained TiO2 nanotubes are highly oriented, with a tube diameter of about 80nm and a tube wall thickness of about 10nm.

[0087] Figure 1 (e) depicts a high-resolution transmission electron microscopy (HRTEM) image of the heterojunction nanocomposite. The measured lattice spacing is 0.269nm, corresponding to the MoS2 crystal plane. The lattice spacing of 0.356nm corresponds to the crystal plane of C3N4. The lattice fringe spacing of 0.241nm can be attributed to the crystal plane of anatase TiO2. The lattice fringes of TiO2, MoS2, and C3N4 can be clearly observed from the HRTEM image, which shows that the crystal structure of the heterojunction nanocomposite is clear.

[0088] Analysis example 2

[0089] The full X-ray photoelectron spectroscopy (XPS) spectrum of the heterojunction nanocomposite material prepared in Example 2 is shown in FIG. 2( a ).

[0090] From Figure 2(a), we can observe the characteristic peaks of all the main elements in the sample, C 1s, N 1s, O 1s, Ti 2p, Mo 3d and S2p. The position of the characteristic peak of each element can help determine its presence and possible chemical state in the sample (heterojunction nanocomposite). Among them, the peaks of C and N indicate the presence of C3N4, while the peaks of Mo and S confirm the presence of MoS2. The peaks of Ti and O indicate the presence of TiO2.

[0091] The high-resolution X-ray photoelectron spectroscopy (XPS) graph of C1s, O 1s, Ti 2p, N 1s, Mo 3d and S2p of the heterojunction nanocomposite material prepared in Example 2 is shown in FIG. 2( b ).

[0092] As shown in Figure 2(b), the sample (heterojunction nanocomposite) is mainly composed of C, N, Mo, S, Ti and O elements. The characteristic peaks of these elements (C 1s, N 1s, Mo 3d, S2p, Ti 2p and O1s) can be clearly observed in the full spectrum Figure 2(a). Among them: The XPS peak positions of MoS2: The peak of Mo 3d 3 / 2 is at 232.0eV; the peak of Mo 3d 5 / 2 is at 228.1eV; the peak of S2p is at 163.0eV. The positions of these peaks indicate that there is Mo in MoS2. 4+ ions. The C 1s peak is located at 285.4 eV. The N 1s spectrum belongs to C=NC (394.9 eV). The O 1s peak corresponds to the Ti-O bond (529.8 eV). The Ti 2p spectrum shows two peaks, located at 459.1 eV (Ti 2p3 / 2) and 464.9 eV (Ti 2p1 / 2).

[0093] Analysis example 3

[0094] Energy dispersive X-ray (EDX) spectroscopy analysis was performed on the products of each stage of the preparation process of Example 1 (titanium dioxide nanotubes, MoS2 / titanium dioxide hybrids, heterojunction nanocomposites). The analysis results are as follows: Figure 3 As shown. Figure 3 It can be seen that the spectrum shows characteristic peaks corresponding to the elements C (carbon), N (nitrogen), O (oxygen), Ti (titanium), Mo (molybdenum) and S (sulfur). The elemental composition of the sample was determined, which is consistent with the XPS analysis results in Analysis Example 2.

[0095] Among them, the analytical data of spectrum 11 is shown in Table 1:

[0096] Table 1 Analysis data of spectrum 11

[0097]

[0098] The analytical data of spectrum 12 is shown in Table 2:

[0099] Table 2 Analysis data of spectrum 12

[0100]

[0101] Example 3

[0102] 1. Catalytic degradation of Rh B (Rhodamine B) using heterojunction nanocomposite materials (TiO2 / MOS2 / C3N4)

[0103] (1) 100 mL of 20 mg / L Rh B solution was added into a cubic quartz cup, and the heterojunction nanocomposite material prepared in Example 1 was inserted into the quartz cup as a working electrode.

[0104] (2) Use light with a wavelength of 400 to 800 nm to irradiate the cubic quartz cup, with a light intensity of 100 mW / cm 2 The solution was stirred at room temperature with a rotor speed of 200 rpm, and samples were taken every 10 min until 60 min, with a sampling volume of 300 μL.

[0105] (3) The sampling results were tested using an ultraviolet spectrophotometer, and a Rh B removal curve was drawn based on the results. Figure 4 shown.

[0106] from Figure 4 It can be seen that the heterojunction nanocomposite electrode exhibits high catalytic efficiency for Rh B molecules. Rh B can be completely decomposed by light radiation for 60 minutes, and the highest degradation kinetic rate k = 0.3056min -1 .

[0107] 2. Under simulated solar radiation and other similar experimental conditions, TiO2, TiO2 / MOS2, TiO2 / C3N4, TiO2 / MOS2 / C3N4 (heterojunction nanocomposite) were used to catalyze the degradation of Rh B. The degradation comparison results are shown in Figure 5 As shown; among them, Figure 5 (a) is a comparison chart of the catalytic degradation effect of each material on Rh B at different times; Figure 5 (b) is a comparison of the degradation kinetic rates of each material for Rh B.

[0108] like Figure 5 As shown in the figure, under the same conditions, the activity of TiO2 / MOS2 / C3N4 electrode is significantly higher than that of other electrodes: TiO2 / C3N4, TiO2 / MOS2, and TiO2. Under 60 minutes of illumination, the degradation rates of RhB by the above photocatalysts are 100%, 78.3%, 69.7%, and 38.2%, respectively. This shows that the enhanced photocatalytic activity of TiO2 / MOS2 / C3N4 is not only attributed to the strong adsorption capacity of the composite material, but also to the formation of a heterostructure with matching energy bands between C3N4, MOS2, and TiO2 nanotubes.

[0109] 3. Under simulated solar radiation and other similar experimental conditions, TiO2 / MOS2 / C3N4 (heterojunction nanocomposite) was used to catalyze the degradation of Rh B for four cycles. The catalytic degradation performance comparison of the heterojunction nanocomposite in four cycles (1st, 2nd, 3rd, 4th) is shown in the figure below. Figure 6 shown.

[0110] according to Figure 6As shown, the photocatalytic degradation performance of the heterojunction nanocomposite material did not show a significant decrease after multiple uses (four cycles), which indicates that the material has good stability and durability and has strong practical applicability.

[0111] Example 4

[0112] 1. Catalytic degradation of PNP (nitrophenol) using heterojunction nanocomposite materials (TiO2 / MOS2 / C3N4)

[0113] (1) 100 mL of 20 mg / L PNP solution was added to a cubic quartz cup, and the heterojunction nanocomposite prepared in Example 2 was inserted into the quartz cup as a working electrode.

[0114] (2) The cubic quartz cup was irradiated with light of wavelengths of 200 to 800 nm, and the solution was stirred at room temperature with a rotor speed of 200 rpm. Sampling was performed every 10 minutes until 40 minutes, and the sampling volume was 300 μL.

[0115] (3) The sampling results are tested using an ultraviolet spectrophotometer, and a PNP removal curve is drawn based on the results. Figure 7 shown.

[0116] from Figure 7 It can be seen that after 40 minutes of continuous visible light irradiation, the characteristic peaks of the PNP model molecule disappeared, which means that the pollutants have been completely eliminated. The highest degradation kinetic rate k = 0.1317min was obtained. -1 .

[0117] 2. Using light radiation with a wavelength of 200 to 800 nm and other similar experimental conditions, TiO2, TiO2 / MOS2, TiO2 / C3N4, and TiO2 / MOS2 / C3N4 (heterojunction nanocomposite materials) were used to catalyze the degradation of PNP. The degradation comparison results are shown in the figure. Figure 8 As shown; among them, Figure 8 (a) is a comparison chart of the catalytic degradation effect of each material on PNP at different time periods; Figure 8 (b) is a comparison of the degradation kinetic rates of PNP by various materials.

[0118] like Figure 8As shown in the figure, under the same conditions, the activity of TiO2 / MOS2 / C3N4 electrode is significantly higher than that of other electrodes: TiO2 / C3N4, TiO2 / MOS2, and TiO2. Under 40 minutes of illumination, the degradation rates of PNP by the above photocatalysts are 100%, 76.2%, 54.9%, and 29.8%, respectively. This indicates that the enhanced photocatalytic activity of TiO2 / MOS2 / C3N4 is not only attributed to the strong adsorption capacity of the composite material, but also to the formation of a heterostructure with matching energy bands between C3N4, MOS2, and TiO2 nanotubes.

[0119] 4. Using 200-800nm ​​wavelength light radiation and other similar experimental conditions, TiO2 / MOS2 / C3N4 (heterojunction nanocomposite) was used to catalyze the degradation of PNP for four cycles. The catalytic degradation performance comparison of the heterojunction nanocomposite in four cycles (1st, 2nd, 3rd, 4th) is shown in the figure below. Fig. 9 shown.

[0120] according to Fig. 9 As shown, the heterojunction nanocomposite material was used to degrade 20 mg / L of PNP. The experiment was repeated four times. The heterojunction nanocomposite material exhibited extremely strong photocatalytic stability and has broad application prospects.

[0121] Analysis example 4

[0122] The heterojunction nanocomposite material obtained in Example 2, TiO2, TiO2 / MOS2, and TiO2 / C3N4 used in Example 4 were subjected to UV-visible absorption spectroscopy analysis. The results are as follows: Fig.10 As shown. Among them, Fig.10 (a) is a comparison of the ultraviolet-visible (UV-vis) absorption spectra of various materials; Fig.10 (b) is a comparison chart of the corresponding Kubelka-Munk transformed reflectance spectra.

[0123] Compared with TiO2, TiO2 / MOS2, and TiO2 / C3N4, the absorption curve of the heterojunction nanocomposite material has significantly enhanced absorption in the visible light region. The absorption edge of the heterojunction nanocomposite material has undergone a significant red shift toward a high wavelength of about 440nm. The band gap energy of the semiconductor can be estimated by Kubelka-Munk transformation, which is calculated to be 1.50, 2.01, 2.80, and 3.20 electron volts, respectively.

[0124] In summary, the above technical solutions of the present invention are only preferred embodiments of the present invention, and the patent scope of the present invention is not limited thereto. All equivalent structural changes made by using the contents of the present invention specification and drawings under the technical concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A heterojunction nanocomposite material, characterized in that: The heterojunction nanocomposite material comprises C3N4 / MoS2 / titanium dioxide nanotube heterojunction nanoparticles, wherein the C3N4 / MoS2 / titanium dioxide nanotube heterojunction nanoparticles are MoS2 / titanium dioxide hybrids with a layered C3N4 coated on the surface; Among them, in the MoS2 / titanium dioxide hybrid, the titanium dioxide nanotubes are highly directional in growth; the MoS2 nanosheets are in the shape of petals and are evenly distributed on the surface of the titanium dioxide nanotubes.

2. A method for preparing the heterojunction nanocomposite material according to claim 1, characterized in that: Includes steps: Providing a molybdenum-sulfur solution; the molybdenum-sulfur solution is an aqueous solution containing a molybdenum source substance and a sulfur source substance; wherein the molar ratio of the molybdenum element to the sulfur element in the molybdenum-sulfur solution is 1-3:15-20; Adding titanium dioxide nanotubes to the molybdenum-sulfur solution for hydrothermal reaction to obtain a MoS2 / titanium dioxide hybrid; wherein, in the MoS2 / titanium dioxide hybrid, the titanium dioxide nanotubes are highly directional in growth; the MoS2 nanosheets are in the shape of petals and are evenly distributed on the surface of the titanium dioxide nanotubes; Providing C3N4 dispersion; The MoS2 / titanium dioxide hybrid is immersed in the C3N4 dispersion and treated at high temperature to obtain a heterojunction nanocomposite material; wherein the temperature of the high temperature treatment is 150-200°C; and the duration of the high temperature treatment is 4-6 hours.

3. The preparation method according to claim 2, characterized in that: The molybdenum source material includes one or more of molybdenum trioxide, ammonium molybdate and sodium molybdate.

4. The preparation method according to claim 2, characterized in that: The sulfur source material is C2H5NS.

5. The preparation method according to claim 2, characterized in that: The temperature of the hydrothermal reaction is 180-220° C.; the duration of the hydrothermal reaction is 6-24 hours.

6. The preparation method according to claim 2, characterized in that: The C3N4 dispersion is obtained by sequentially subjecting the nitrogen-containing organic matter to high-temperature calcination, grinding, protonation and ultrasonic dispersion to obtain the C3N4 dispersion; Wherein, the nitrogen-containing organic matter includes one or more of melamine, cyanuric acid, melamine resin and urea.

7. The preparation method according to claim 6, characterized in that: The temperature of the high temperature calcination treatment is 450-550° C.; the duration of the high temperature calcination treatment is 12-24 hours.

8. The preparation method according to claim 2, characterized in that: After the high temperature treatment step, the product after the high temperature treatment is further subjected to washing and vacuum drying to obtain the heterojunction nanocomposite material.

9. Use of the heterojunction nanocomposite material according to claim 1 or the heterojunction nanocomposite material prepared by the preparation method according to any one of claims 2 to 8, characterized in that: The heterojunction nanocomposite material is inserted into an organic pollutant solution as a working electrode and subjected to visible light irradiation treatment to obtain a pollutant decomposed solution; wherein the visible light has a wavelength of 400 to 800 nm and the visible light irradiation treatment lasts for 30 to 80 minutes.

10. The use according to claim 9, characterized in that: The concentration of the organic pollutant solution is 10 to 50 mg / L; The organic pollutant solution includes one or more of p-nitrophenol, methyl orange, methylene blue, phenol, rhodamine, fluorescent yellow, and 2,4-dichlorophenoxyacetic acid.

Citation Information

Patent Citations

  • Preparation method of Pt-loaded sulfur-rich molybdenum disulfide boundary site modified titanium dioxide nanotube array

    CN108505098A

  • Gold nanoparticle modified molybdenum sulfide / titanium oxide composite material and preparation method thereof

    CN108855147A

  • Application of MoS2@C3N4 composite nanomaterial as mimic enzyme

    CN109482216A

  • Multi-element nanotube composite material for removing aldehyde through visible light catalysis and preparation method of multi-element nanotube composite material

    CN114904551A

  • Methods of producing a nanocomposite heterojunction photocatalyst

    WO2019021189A1